Nebulized dexmedetomidine in the treatment of obstetric post-dural puncture headache: two case reports - Jeffrey Thomas; Leonard J. Soloniuk; Chris Mehdizadeh; Peter Cheng; Ashish Sinha (BMC Anesthesiology)
Abstract Post-dural puncture headache (PDPH) is a debilitating complication of neuraxial anesthesia, particularly prevalent in obstetric patients, usually characterized by a postural headache. PDPH is hypothesized to result from cerebrospinal fluid leakage through a dural puncture, triggering symptoms like neck stiffness and subjective hearing changes. While conservative measures are common for treatment, more refractory cases may require invasive interventions such as an epidural blood patch (EBP). Recent studies have shown promise in using nebulized dexmedetomidine (nDEX) for PDPH, offering a non-invasive alternative to EBP. Two case presentations illustrate the efficacy of nDEX in resolving PDPH symptoms rapidly and completely. These cases underscore the need for exploring novel therapeutic options, especially in obstetric patients where safe and prompt relief is essential for maternal and newborn well-being. While the EBP remains the gold standard, its limitations of accessibility and invasiveness highlight the significance of investigating alternatives like nDEX.